1994
DOI: 10.1084/jem.179.1.323
|View full text |Cite
|
Sign up to set email alerts
|

CDR3 length in antigen-specific immune receptors.

Abstract: SummaryIn both immunoglobulins (Ig) and T cell receptors (TCR.), the rearrangement of V, D, and J region sequence elements during lymphocyte maturation creates an enormous degree of diversity in an area referred to as the complementarity determining region 3 (CDR3) loop. Variations in the particular V, D, and J elements used, precise points of recombination, and random nucleotide addition all lead to extensive length and sequence heterogeneity. CDR3 loops are often critical for antigen binding in Igs and appea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
294
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 459 publications
(325 citation statements)
references
References 20 publications
25
294
1
Order By: Relevance
“…One determinant in the selection process could be the difference in CDR3 length between TCR␥ and TCR␦ chains. Rock et al 43 demonstrated in their study that the CDR3 of TCR␦ chains is on average longer than the CDR3 of TCR␥ chains. In our series of TCR␥␦ + T-ALL we also see that the CDR3 length of expressed TCR␦ chains is on average longer than that of TCR␥ chains, but in individual cases the TCR␦ CDR3 was sometimes found to be equal to or even smaller than the TCR␥ CDR3 (data not shown).…”
Section: Tablementioning
confidence: 95%
“…One determinant in the selection process could be the difference in CDR3 length between TCR␥ and TCR␦ chains. Rock et al 43 demonstrated in their study that the CDR3 of TCR␦ chains is on average longer than the CDR3 of TCR␥ chains. In our series of TCR␥␦ + T-ALL we also see that the CDR3 length of expressed TCR␦ chains is on average longer than that of TCR␥ chains, but in individual cases the TCR␦ CDR3 was sometimes found to be equal to or even smaller than the TCR␥ CDR3 (data not shown).…”
Section: Tablementioning
confidence: 95%
“…In contrast to / T cells, there is no proven paradigm for the nature of the ligands that are recognized by / T cells, although recent studies suggest a population of V 2-expressing / T cells can recognize small, non-peptide molecules [53,54]. However, recent reports suggest there are fundamental differences in the pathways by which ligands are processed and presented to / compared with / T cells [51,52,55], and it has been proposed that / T cells recognize ligands in a manner more analogous to that of antibody [41].…”
Section: Discussionmentioning
confidence: 99%
“…Lengths of the CDR3 domains of translated TCR transcripts were determined as described before [24,41]. Briefly, the distance was calculated between the conserved cysteine at position 88, which is encoded by the 3 0 TCRDV region, and the conserved GXG triplet, which is encoded by all TCRDJ regions, and eight amino acids were subtracted [41][42][43].…”
Section: Cdr3 Lengthmentioning
confidence: 99%
“…Thus, CDR3 regions of the cd TCRs resemble Ig CDRs in terms of length and variability. 15 As is the case with Ig heavy and light chains, respectively, TCR-d has extensive CDR3s whereas TCR-c has short CDR3s. Moreover, TCR-d CDR3s are far more diverse, similar to IgH CDR3s.…”
Section: Mechanism Of Ligand Recognitionmentioning
confidence: 95%